2013
DOI: 10.4103/0300-1652.108895
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to postnatal care and exclusive breastfeeding among urbanwomen in southeastern Nigeria

Abstract: Background:Available evidence shows that only a small proportion of Nigerian women access postnatal care and practice exclusive breastfeeding. Given that both interventions are critical to the survival of both the mother and the new born, it is important to identify factors that militate against an effective postnatal care and exclusive breastfeeding in the country, in order to scale up services. The aim was to determine the major barriers to postnatal care and exclusive breastfeeding among urban women in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 5 publications
8
54
0
Order By: Relevance
“…Ten studies were cross-sectional (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) , three were mixed-methods (21)(22)(23) and two were prospective cohort studies (24,25) . Five crosssectional studies reported a significant positive association between ANC attendance and EBF (14)(15)(16)18,20) . Women with attendance at any ANC visit were twice as likely to practise EBF compared with women who did not attend ANC (36·4 v. 18·2 %, respectively; P = 0·00, χ 2 test) (16) .…”
Section: Prenatal-related Barriers To Exclusive Breast-feedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies were cross-sectional (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) , three were mixed-methods (21)(22)(23) and two were prospective cohort studies (24,25) . Five crosssectional studies reported a significant positive association between ANC attendance and EBF (14)(15)(16)18,20) . Women with attendance at any ANC visit were twice as likely to practise EBF compared with women who did not attend ANC (36·4 v. 18·2 %, respectively; P = 0·00, χ 2 test) (16) .…”
Section: Prenatal-related Barriers To Exclusive Breast-feedingmentioning
confidence: 99%
“…Pakistan Cross-sectional X X Ssenyonga et al (38) 353 Uganda Cross-sectional X Suresh et al (53) 400 India Cohort Susiloretni et al (20) 541 Indonesia Cross-sectional X X Tamiru et al (22) 382 Ethiopia Cross-sectional X X Tiwari et al (15) 279 India Cross-sectional X Ugboaja et al (16) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They also believed that mother's milk does not meet nutritional requirements of a baby, has no effect on baby's weight and prohibits sexual intercourse while breast- feeding [11]. In southeastern Nigeria, the critical indicators for non-practice of EBF included maternal unwillingness, mother's being stressful and the feeling that EBF is unimportant [12]. In Southwest Nigeria, the barriers to breastfeeding were: maternal health problem, not enough to satisfy baby's hunger, the need to return to work, mother-in-law's demand, breast pain, and a fear of child's breast milk addiction [13].…”
Section: Discussionmentioning
confidence: 99%
“…Also, general discussions about breastfeeding challenges, promoting EBF through education and extending maternity leave are suggested for better outcomes [12][13][14][15][16]. Strategies to clarify the misconceptions about breastfeeding's insufficiency for an infant's growth need to be strengthened.…”
Section: Practice Recommendationsmentioning
confidence: 99%